2021
DOI: 10.3389/fcell.2021.702590
|View full text |Cite
|
Sign up to set email alerts
|

In situ Synthesized Monosodium Urate Crystal Enhances Endometrium Decidualization via Sterile Inflammation During Pregnancy

Abstract: High level of uric acid (UA) is the major origin of gout, and is highly associated with various pregnant complications, such as preeclampsia and gestational diabetes. However, UA’s level and role in the very early stage of pregnancy has not been uncovered. This study aims to investigate the relevance of serum UA and decidualization, an essential process for the establishment and maintenance of pregnancy in women and mice during the early stage of pregnancy. In this study, we first proved that expression level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Activated fibroblasts play key roles in the injury response, tumorigenesis, fibrosis, and inflammation through secreting different factors in different physiological or pathological processes [61]. Myofibroblast marker α-SMA has been shown to be one of the important markers of early decidualization in primates[20], and sterile inflammatory secretion of products such as ATP and uric acid after injury has been shown to stimulate fibroblast activation [28; 29] and uterine decidualization [26; 27], so we speculate that fibroblast activation is strongly correlated with decidualization. Because TNC, SPARC, FSP1 and ACTIVIN A were all identified during fibroblast activation, we examined the role of each of these markers during mouse decidualization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated fibroblasts play key roles in the injury response, tumorigenesis, fibrosis, and inflammation through secreting different factors in different physiological or pathological processes [61]. Myofibroblast marker α-SMA has been shown to be one of the important markers of early decidualization in primates[20], and sterile inflammatory secretion of products such as ATP and uric acid after injury has been shown to stimulate fibroblast activation [28; 29] and uterine decidualization [26; 27], so we speculate that fibroblast activation is strongly correlated with decidualization. Because TNC, SPARC, FSP1 and ACTIVIN A were all identified during fibroblast activation, we examined the role of each of these markers during mouse decidualization.…”
Section: Discussionmentioning
confidence: 99%
“…During the inflammatory phase, the release of these DAMP molecules is able to stimulate the conversion of fibroblasts to αSMA-expressing myofibroblasts [25]. We recently demonstrated that secreted ATP or uric acid under artificial decidualization can induce mouse decidualization [26; 27]. It has been shown that ATP or uric acid can also stimulate fibroblast activation [28; 29].…”
Section: Introductionmentioning
confidence: 99%
“…Further study has shown that the expression of SRC is necessary for invasion and migration of human decidual stromal cells, which exerts vital functions in embryo implantation and human pregnancy [ 47 ]. Prostaglandin G/H synthase 2 (PTGS2) is related to the regulation of inflammatory response, the regulation of which influences the decidualization response of endometrial stromal cells [ 48 ]. Numerous studies have shown that PTGS2 is identified as important regulators of early pregnancy events and plays a vital role in human decidualization and vascularization of the endometrial stroma [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…ATP, uric acid, HMGB1 and cell-free fetal DNA are recently identified members of DAMP family ( 12 ). Both ATP and uric acid have been shown to play a role during decidualization ( 13 , 14 ). Both Hmgb1 mRNA and proteins are highly detected in mouse preimplantation uterus ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%